Dynamics and capture of space-charge dominated electron beams in crossed-fields system - Agafonov, A.V. (Вопросы атомной науки и техники, 1999)
Problems of nonlinear dynamics of space-charge
dominated electron beams in crossed ExB-fields are
discussed from the point of view of the investigation of
schemes of intense electron beam formation for
compact cyclic accelerators and for high-efficiency
relativistic magnetrons. The review of the results of
computer simulations of an electron clouds formation
due to nonlinear azimuthal instability inside magnetron
is given. A scheme of electron storage and capture of
electron beams in crossed fields is proposed.